EU-NICE, Eurasian University Network for International Cooperation in Earthquakes - Faggella, M. (2012)
Despite the remarkable scientific advancements of earthquake engineering and seismology in many countries, seismic risk is still growing at a high rate in the world’s most vulnerable communities. Successful practices have shown that a community’s capacity to manage and reduce its seismic risk relies on capitalization on policies, on technology and research results. An important role is played by education, than contribute to strengthening technical curricula of future practitioners and researchers through university and higher education programmes. In recent years an increasing number of initiatives have been launched in this field at the international and global cooperation level. Cooperative international academic research and training is key to reducing the gap between advanced and more vulnerable regions. EU-NICE is a European Commission funded higher education partnership for international development cooperation with the objective to build capacity of individuals who will operate at institutions located in seismic prone Asian Countries. The project involves five European Universities, eight Asian universities and four associations and NGOs active in advanced research on seismic mitigation, disaster risk management and international development. The project consists of a comprehensive mobility scheme open to nationals from Afghanistan, Bangladesh, China, Nepal, Pakistan, Thailand, Bhutan, India, Indonesia, Malaysia, Maldives, North Korea, Philippines, and Sri Lanka who plan to enrol in school or conduct research at one of five European partner universities in Italy, Greece and Portugal. During the 2010-14 time span a total number of 104 mobilities are being involved in scientific activities at the undergraduate, masters, PhD, postdoctoral and academic-staff exchange levels. This high number of mobilities and activities is selected and designed so as to produce an overall increase of knowledge that can result in an impact on earthquake mitigation. Researchers, future policymakers and practitioners build up their curricula over a range of disciplines in the fields of engineering, seismology, disaster risk management and urban planning. Specific educational and research activities focus on earthquake risk mitigation related topics such as: anti-seismic structural design, structural engineering, advanced computer structural collapse analysis, seismology, experimental laboratory studies, international and development issues in disaster risk management, social-economical impact studies, international relations and conflict resolution.